Determinants of private investments in South Africa - Sesele, Mmathabo (Research of GSB, 2018)
This paper reviews the causal connection between private investment; interest rates and macroeconomic uncertainty in South Africa on a yearly time series data range between 1980 and 2014. This research was encouraged by the continually weakening private investment in South Africa relative to total investment. There is a need to turn around this pattern. This research contributes towards a greater comprehension of the variables and their direction of impact in the examination of the pattern of private investments and additionally, the impacts of interest rate and macroeconomic uncertainty on private investment in SA. The study employs an ARDL model for co-integration to explore the presence of a long-run relationship between the variables and the granger causality within VECM to check the interrelations among the series. The findings reveal that all variables are co-integrated to suggest the existence of a long-run relationship among private investment, long-term interest rates and bond spread. The results show that macroeconomic uncertainty exerts an adverse influence on private investment, in accordance with economic theory. In contrast to the theory, the long-term interest rates coefficient is positive and significant in the projected equation. Therefore, the conclusion is that the interest rate contributes toward the reduction in private investment. Keeping in mind the end goal to resuscitate private investment, government ought to consider receiving approaches that lift total request, offering greater venture motivations, facilitating credit limitations by forming a more productive and vigorous money-related framework, decreasing macroeconomic vulnerabilities, encouraging foundation improvement, and empowering inflows of outside speculation.